Quality assurance guidelines for superficial hyperthermia clinical trials: I. Clinical requirements. (19th May 2017) - Trefná, Hana Dobšíček; Crezee, Hans; Schmidt, Manfred; Marder, Dietmar; Lamprecht, Ulf; Ehmann, Michael; Hartmann, Josefin; Nadobny, Jacek; Gellermann, Johanna; van Holthe, Netteke; Ghadjar, Pirus; Lomax, Nicoletta; et al.
Abstract: Quality assurance guidelines are essential to provide uniform execution of clinical trials and treatment in the application of hyperthermia. This document provides definitions for a good hyperthermia treatment and identifies the clinical conditions where a certain hyperthermia system can or cannot adequately heat the tumour volume. It also provides brief description of the characteristics and performance of the current electromagnetic (radiative and capacitive), ultrasound and infra-red heating techniques. This information helps to select the appropriate heating technique for the specific tumour location and size, and appropriate settings of the water bolus and thermometry. Finally, requirements of staff training and documentation are provided. The guidelines in this document focus on the clinical application and are complemented with a second, more technical quality assurance document providing instructions and procedure to determine essential parameters that describe heating properties of the applicator for superficial hyperthermia. Both sets of guidelines were developed by the ESHO Technical Committee with participation of senior STM members and members of the Atzelsberg Circle.